Influence of Meteorological Factors on Forage and Seed Productivity of Cenchrus ciliaris - Rao, A S; Singh, K C (Annals of Arid Zone, 2016)
High temperatur~s and windspeeds prevailing in the arid region at Jodhpur had negative correlation whereas, rainfall, humidity and rainy days had positive correlations on forage and seed yield of Cenchrus ciliaris. Seed yield of C. ciliaris increased from 67 to 153 kg ha-1 with a gradual increase in quantum of seasonal rainfall from 150 to 400 mm. Rainfall at flowering seed setting stages reduced the seed yield. Only in good rainfall years, application of N and P to the grass had a significant effect on forage, but such a response was not observed on seed yield due to rain and high winds at seed setting/maturity stages. The forage and seed yield relationships of C. ciliaris showed that there was a gradual increase in seed yield from 59 to 248 kg ha-1 with increase in the forage yield from 909 to 1565 kg ha-1Â .The yield index (T/Tp) computed using RANGETECH model showed that in general with the increase in yield index value from 0.40 to 0.85, the seed production of C. ciliaris increased from 0 to 172 kg ha -1. Rainfall explained 1% seed and 36% forage yield, whereas the yield index was useful for prediction of variations upto 24% seed and 76% forage yield.